THE REPRESENTATION OF SOCIAL ACTORS IN FIRST 100 DAYS OF OFFICE OF JOKOWI-BASUKI - Nursya'bani, Fira (2014)
This study presents the analysis of how the national mass media deliver their ideological point of view to the readers in their online articles regading a political issue in Joko Widodo and Basuki Tjahja Purnama first 100 days of office. It was aimed at investigating the way social actors are represented in the text and to uncover the ideologies underlying the representation. The data were obtained from ten online articles from different nationwide media published in 22 January 2013. A qualitative method was employed to analyse the selected data. The data were analysed based on the sociosemantic approach proposed by Van Leeuwen (2008). The findings showed that Jokowi as the governor of Jakarta was dominated the occurrences as an active participant. Moreover, different impression was shown where the active roles were always associated with Jokowi and the passive roles were always associated with Jakarta. The findings also revealed that the possible ideologies that can be inferred from the representation were democracy and Jokowi as the "city rescuer." Studi ini mengemukakan analisis mengenai bagaimana media masa nasional menyampaikan sudut pandang ideologi tertentu kepada pembaca dalam artikel online mengenai isu politik yaitu 100 hari pertama Joko Widodo dan Basuki Tjahja Purnama di Pemerintahan. Studi ini bertujuan untuk meneliti bagaimana aktor sosial direpresentasikan di dalam teks dan untuk membongkar ideology yang mendasari representasi tersebut. Data yang digunakan dalam studi ini diperoleh dari sepuluh artikel online dari sepuluh koran online berbeda yang semuanya diterbitkan pada 22 Januari 2013. Metodologi kualitatif dipakai dalam studi ini untuk menganalisis data yang telah dipilih. Data dianalisis menggunakan pendekatan sociosemantic yang dikemukakan oleh Van Leeuwen di tahun 2008. Studi ini menunjukan bahwa Jokowi, sebagai gubernur Jakarta, mendominasi kemunculan aktor sosial sebagai partisipan yang aktif di dalam teks. Selain itu, kesan lain terlihat ketika peran aktif selalu dikaitkan pada sosok Jokowi, sedangkan peran pasif selalu dikaitkan pada Jakarta. Studi ini juga menyatakan bahwa ideologi yang dapat disimpulkan dari representasi tersebut adalah demokrasi dan Jokowi sebagai "penyelamat kota."